Cost-effectiveness of rosuvastatin in comparison with generic atorvastatin and simvastatin in a Swedish population at high risk of cardiovascular events - Gandhi SK; Jensen MM; Fox KM; Smolen L; Olsson AG; Paulsson T (Dove Medical Press, 2012)
Sanjay K Gandhi1, Marie M Jensen2, Kathleen M Fox3, Lee Smolen4, Anders G Olsson5, Thomas Paulsson61AstraZeneca LP, Wilmington, DE, USA; 2AstraZeneca, Lund, Sweden; 3Strategic HealthCare Solution, Monkton, MD; 4Medical Decision Modeling Inc, Indianapolis, IN, USA; 5Department of Medical and Health Sciences, Linkoping University, and Stockholm Heart Center, Stockholm; 6AstraZeneca, Sodertalje, SwedenBackground: To assess the long-term cost-effectiveness of rosuvastatin therapy compared with generic simvastatin and generic atorvastatin in reducing the incidence of cardiovascular events and mortality in a Swedish population with Framingham risk ≥20%.Methods: A probabilistic Monte Carlo simulation model based on data from JUPITER (the Justification for the Use of statins in Prevention: an Intervention Trial Evaluating Rosuvastatin) was used to estimate the long-term cost-effectiveness of rosuvastatin 20 mg daily versus simvastatin or atorvastatin 40 mg for the prevention of cardiovascular death and morbidity. The three-stage model included cardiovascular event prevention simulating the 4 years of JUPITER, initial prevention beyond the trial, and subsequent cardiovascular event prevention. A Swedish health care payer perspective (direct costs only) was modeled for a lifetime horizon, with 2008/2009 as the costing period. Univariate and probabilistic sensitivity analyses were performed.Results: The incremental cost per quality-adjusted life-year (QALY) gained with rosuvastatin 20 mg over simvastatin or atorvastatin 40 mg ranged from SEK88,113 (rosuvastatin 20 mg versus simvastatin 40 mg; Framingham risk ≥30%; net avoidance of 34 events/1000 patients) to SEK497,542 (versus atorvastatin 40 mg: Framingham risk ≥20%; net avoidance of 11 events/1000 patients) over a lifetime horizon. Probabilistic sensitivity analyses indicated that at a willingness-to-pay threshold of SEK500,000/QALY, rosuvastatin 20 mg would be cost-effective for approximately 75%–85% of simulations relative to atorvastatin or simvastatin 40 mg. Sensitivity analyses indicated the findings to be robust.Conclusion: Rosuvastatin 20 mg is cost-effective over a lifetime horizon compared with generic simvastatin or atorvastatin 40 mg in patients at high cardiovascular risk in Sweden.Keywords: cardiovascular disease, cost-benefit analysis, cost-effectiveness, rosuvastatin, simvastatin, atorvastatin, generic, high risk